Genealogy of the Concept of Wasathiyyah in Islamic Education: A Critical Analysis of Classical and Digital Texts - Wartinah Wartinah; Ichsan Ichsan; Sibawaihi Sibawaihi (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
This research aims to examine the conceptual dynamics of wasathiyyah (Islamic moderation) in the context of Islamic education by conducting a genealogical exploration of classical texts and a critical analysis of current digital representations. The method used is qualitative, with a literature study and critical discourse analysis of two main corpora. First, classical Islamic literature, including tafsir, hadith, and works of authoritative scholars. And secondly, digital content such as online articles, social media, and da'wah videos. The findings show that in classical texts, wasathiyyah is understood as an epistemological principle that harmonizes reason and revelation and rejects extremism. In the digital space, that meaning is often simplified or even distorted due to the influence of ideological interests and populist communication patterns. The challenge for Islamic education in maintaining its scientific authority and transformative value arises from this phenomenon. Thus, the integration of classical scientific heritage and critical religious digital literacy is a key strategy in building a contextual, reflective, and value-rooted Islamic education paradigm based on the principle of rahmatan lil-‘alamin.